Prophylactic Effect of Aegle Marmelos Leaves Against Complete Freunds Adjuvant (Cfa) Induced Arthritis - V, Desai Nilesh; N, Patkar Atul; A, Shinde Shilpa; V, Pandav A. (Asian Journal of Pharmaceutical Research and Development, 2013)
Rheumatoid arthritis (RA) is a chronic crippling, skeleton-muscular disorder having nearest approximation to human rheumatoid arthritis for which there is currently no medicine available effecting a permanent cure. Even modern drugs used for the amelioration of the symptoms, offer only temporary relief and also produce severe side effects. This work was aimed at the scientific validation of the ethno-pharmacological claim about Aegle marmelos and its anti-arthritic property. In the present study, anti-arthritic activity of aqueous extract of Aegle marmelos (AEAM) is done by prophylactic model of Complete freunds adjuvant (CFA) induced arthritis. Parameters such as paw edema, paw diameter and changes in body weight during arthritic condition was corrected on treatment with AEAM. Serum parameters such as SGOT, SGPT, ALP, and Total protein were also estimated for assessing the anti- arthritic potential of AEAM. The results of the current investigation concluded AEAM possess a significant anti-arthritic activity against CFA induced arthritis model and justifying its therapeutic role in arthritic condition. The observed antiarthritic activity may be due to the presence of phytoconstituents such as alkaloid and flavonoids.